Digitizing Agriculture and Empowering Farmers: A Study of Technology Adoption Among Small Ruminant Farmers in Terengganu - Hayuni, M; Lukman, Z.M; Azlini, C.; Norshahira, O (Universitas Muhammadiyah Palu, 2025)
Rural poverty in Terengganu is closely tied to the limitations of traditional farming practices and the underutilization of modern technology. This study investigates the socioeconomic benefits of adopting agricultural technology among low-income small ruminant farmers in the region. By categorizing respondents into adopters and non-adopters, and analyzing their practices using survey questionnaires and independent sample t-tests, the study found that technology adopters significantly outperformed their peers in productivity (p<0.05) and entrepreneurial innovation. These findings underscore the transformative potential of technology in improving livelihoods, reducing poverty, and fostering sustainable agricultural development. The research calls for targeted policy interventions and support systems to facilitate broader technology adoption and bridge the digital divide in rural farming communities.